DEFINITION ty3_gen_appl_nf2()
TYPE =
       g:G
         .c:C
           .w:T
             .v:T
               .x:T
                 .ty3 g c (THead (Flat Appl) w v) x
                   (ex4_2
                        T
                        T
                        λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                        λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                        λu:T.λ:T.ty3 g c w u
                        λu:T.λt:T.nf2 c (THead (Bind Abst) u t))
BODY =
        assume gG
        assume cC
        assume wT
        assume vT
        assume xT
        suppose Hty3 g c (THead (Flat Appl) w v) x
          by (ty3_gen_appl . . . . . H)
          we proved 
             ex3_2
               T
               T
               λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
               λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
               λu:T.λ:T.ty3 g c w u
          we proceed by induction on the previous result to prove 
             ex4_2
               T
               T
               λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
               λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
               λu:T.λ:T.ty3 g c w u
               λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
             case ex3_2_intro : x0:T x1:T H0:pc3 c (THead (Flat Appl) w (THead (Bind Abst) x0 x1)) x H1:ty3 g c v (THead (Bind Abst) x0 x1) H2:ty3 g c w x0 
                the thesis becomes 
                ex4_2
                  T
                  T
                  λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                  λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                  λu:T.λ:T.ty3 g c w u
                  λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                   (H_x
                      by (ty3_correct . . . . H1)
ex T λt:T.ty3 g c (THead (Bind Abst) x0 x1) t
                   end of H_x
                   (H3consider H_x
                   we proceed by induction on H3 to prove 
                      ex4_2
                        T
                        T
                        λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                        λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                        λu:T.λ:T.ty3 g c w u
                        λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                      case ex_intro : x2:T H4:ty3 g c (THead (Bind Abst) x0 x1) x2 
                         the thesis becomes 
                         ex4_2
                           T
                           T
                           λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                           λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                           λu:T.λ:T.ty3 g c w u
                           λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                            (H_x0
                               by (ty3_correct . . . . H2)
ex T λt:T.ty3 g c x0 t
                            end of H_x0
                            (H5consider H_x0
                            we proceed by induction on H5 to prove 
                               ex4_2
                                 T
                                 T
                                 λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                 λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                 λu:T.λ:T.ty3 g c w u
                                 λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                               case ex_intro : x3:T H6:ty3 g c x0 x3 
                                  the thesis becomes 
                                  ex4_2
                                    T
                                    T
                                    λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                    λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                    λu:T.λ:T.ty3 g c w u
                                    λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                                     (H7
                                        by (ty3_sn3 . . . . H4)
sn3 c (THead (Bind Abst) x0 x1)
                                     end of H7
                                     (H_x1
                                        by (nf2_sn3 . . H7)
ex2 T λu:T.pr3 c (THead (Bind Abst) x0 x1) u λu:T.nf2 c u
                                     end of H_x1
                                     (H8consider H_x1
                                     we proceed by induction on H8 to prove 
                                        ex4_2
                                          T
                                          T
                                          λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                          λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                          λu:T.λ:T.ty3 g c w u
                                          λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                                        case ex_intro2 : x4:T H9:pr3 c (THead (Bind Abst) x0 x1) x4 H10:nf2 c x4 
                                           the thesis becomes 
                                           ex4_2
                                             T
                                             T
                                             λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                             λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                             λu:T.λ:T.ty3 g c w u
                                             λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                                              (H11
                                                 by (pr3_gen_abst . . . . H9)

                                                    ex3_2
                                                      T
                                                      T
                                                      λu2:T.λt2:T.eq T x4 (THead (Bind Abst) u2 t2)
                                                      λu2:T.λ:T.pr3 c x0 u2
                                                      λ:T.λt2:T.b:B.u:T.(pr3 (CHead c (Bind b) u) x1 t2)
                                              end of H11
                                              we proceed by induction on H11 to prove 
                                                 ex4_2
                                                   T
                                                   T
                                                   λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                                   λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                                   λu:T.λ:T.ty3 g c w u
                                                   λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                                                 case ex3_2_intro : x5:T x6:T H12:eq T x4 (THead (Bind Abst) x5 x6) H13:pr3 c x0 x5 H14:b:B.u:T.(pr3 (CHead c (Bind b) u) x1 x6) 
                                                    the thesis becomes 
                                                    ex4_2
                                                      T
                                                      T
                                                      λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                                      λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                                      λu:T.λ:T.ty3 g c w u
                                                      λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
                                                       (H15
                                                          we proceed by induction on H12 to prove nf2 c (THead (Bind Abst) x5 x6)
                                                             case refl_equal : 
                                                                the thesis becomes the hypothesis H10
nf2 c (THead (Bind Abst) x5 x6)
                                                       end of H15
                                                       (H16
                                                          by (H14 . .)
                                                          we proved pr3 (CHead c (Bind Abst) x5) x1 x6
                                                          by (pr3_head_12 . . . H13 . . . previous)
pr3 c (THead (Bind Abst) x0 x1) (THead (Bind Abst) x5 x6)
                                                       end of H16
                                                       (h1
                                                          by (pr3_thin_dx . . . H16 . .)
                                                          we proved 
                                                             pr3
                                                               c
                                                               THead (Flat Appl) w (THead (Bind Abst) x0 x1)
                                                               THead (Flat Appl) w (THead (Bind Abst) x5 x6)
                                                          by (pc3_pr3_conf . . . H0 . previous)
pc3 c (THead (Flat Appl) w (THead (Bind Abst) x5 x6)) x
                                                       end of h1
                                                       (h2
                                                          (h1
                                                             by (ty3_sred_pr3 . . . H16 . . H4)
ty3 g c (THead (Bind Abst) x5 x6) x2
                                                          end of h1
                                                          (h2
                                                             by (pc3_pr3_r . . . H16)
pc3 c (THead (Bind Abst) x0 x1) (THead (Bind Abst) x5 x6)
                                                          end of h2
                                                          by (ty3_conv . . . . h1 . . H1 h2)
ty3 g c v (THead (Bind Abst) x5 x6)
                                                       end of h2
                                                       (h3
                                                          (h1by (ty3_sred_pr3 . . . H13 . . H6) we proved ty3 g c x5 x3
                                                          (h2
                                                             by (pc3_pr3_r . . . H13)
pc3 c x0 x5
                                                          end of h2
                                                          by (ty3_conv . . . . h1 . . H2 h2)
ty3 g c w x5
                                                       end of h3
                                                       by (ex4_2_intro . . . . . . . . h1 h2 h3 H15)

                                                          ex4_2
                                                            T
                                                            T
                                                            λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                                            λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                                            λu:T.λ:T.ty3 g c w u
                                                            λu:T.λt:T.nf2 c (THead (Bind Abst) u t)

                                                 ex4_2
                                                   T
                                                   T
                                                   λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                                   λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                                   λu:T.λ:T.ty3 g c w u
                                                   λu:T.λt:T.nf2 c (THead (Bind Abst) u t)

                                        ex4_2
                                          T
                                          T
                                          λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                          λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                          λu:T.λ:T.ty3 g c w u
                                          λu:T.λt:T.nf2 c (THead (Bind Abst) u t)

                               ex4_2
                                 T
                                 T
                                 λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                                 λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                                 λu:T.λ:T.ty3 g c w u
                                 λu:T.λt:T.nf2 c (THead (Bind Abst) u t)

                      ex4_2
                        T
                        T
                        λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                        λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                        λu:T.λ:T.ty3 g c w u
                        λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
          we proved 
             ex4_2
               T
               T
               λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
               λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
               λu:T.λ:T.ty3 g c w u
               λu:T.λt:T.nf2 c (THead (Bind Abst) u t)
       we proved 
          g:G
            .c:C
              .w:T
                .v:T
                  .x:T
                    .ty3 g c (THead (Flat Appl) w v) x
                      (ex4_2
                           T
                           T
                           λu:T.λt:T.pc3 c (THead (Flat Appl) w (THead (Bind Abst) u t)) x
                           λu:T.λt:T.ty3 g c v (THead (Bind Abst) u t)
                           λu:T.λ:T.ty3 g c w u
                           λu:T.λt:T.nf2 c (THead (Bind Abst) u t))